FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Asih Mustikorini; Darsono Darsono (Diponegoro Journal of Accounting, 2019)
This study was aimed to examine the effect of ownership concentration, board of commissioner size, firm size, earning management, foreign ownership and firm investment on firm value of manufacturing company in Indonesia This study used secondary data which was annual reports retrieved from Indonesia Stock Exchange (IDX) website. This study used purposive sampling method. Population in this study were manufacturing company listed on the Indonesia Stock Exchange in 2016-2018. 166 companies were selected as samples from 414 companies as the population during 2016-2018. The research method used in this study was multiple linear regression.The result of this study indicated that board of commissioner size had a positive and significant effect on firm value. Firm size, earning management and foreign ownership had a negative and significant effect on firm value, while ownership concentration and firm investment had no effect on firm value.